WORKSHOP MENYULAM SEBAGAI PENINGKATAN POTENSI DAN KREATIVITAS LANSIA - Lia, Della Ayu Zonna; Tirtasari, Berliana Nadia Rakhma; Yakin, Fadillah Ainul; Mustika, Fernanda Ayu; Shevchenko, Kevin Henry; Mutaqqin, Robbi Habbal (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Elderly or can be called the elderly is a group of parents aged 45 years and over. Some of the elderly spend a lot of time at home, one of which is due to the condition of the body's declining stamina, causing a lack of active and productive activities that can be done by the elderly. Productive activities will help the elderly to keep moving and doing fun activities, so that their body and soul will feel better. One of the productive activities that can be done by the elderly is embroidery. The implementation of embroidery training activities for elderly mothers is carried out in four stages systematically consisting of (1) preparation; (2) implementation; (3) closing; and (4) preparation of reports. The purpose of this service activity is to organize productive activities for the elderly to increase the potential and creativity of the elderly of Talok Village.